Association between Resilience and Professional Quality of Life among Nurses Working in Intensive Care Units - N Gerami Nejad; M Hosseini; SM Mousavi Mirzaei; Z Ghorbani Moghaddam (Iran University of Medical Sciences, 2019)
units (ICUs) could decrease their professional quality of life, thereby leading to mental issues, such as the declined quality of patient care and other consequences. Given the importance of resilience in difficult situations, the present study aimed to determine the association of resilience with the professional quality of life of ICU nurses. Materials & Methods: This descriptive-correlational study was conducted on 200 nurses working in the ICUs of the teaching hospitals affiliated to Birjand University of Medical Sciences in South Khorasan province, Iran in 2018. The participants were selected via census sampling. Data were collected using Connor-Davidson resilience questionnaire and Stamm professional quality of life scale. Data analysis was performed in SPSS version 16 using descriptive and inferential statistics, including t-test, analysis of variance (ANOVA), and Kruskal-Wallis test. Results: The mean total score of resilience was 60.31±20.39. As for the three dimensions of the quality of professional life, the mean score of compassion fatigue was 34.54±9.13, the mean score of job burnout was 24.06±5.70, and the mean score of secondary trauma was 26.49±7.86. Moreover, an inverse, significant correlation was observed between resilience and compassion fatigue (r=-0.44; P=0.001). Conclusion: Considering the average level of the professional quality of life in the nurses, special attention must be paid to the influential factors in professional quality of life. In addition, due to the significant association between resilience and compassion fatigue, incorporating resilience-promoting strategies into the nursing curriculum is recommended.